Effects of emamectin benzoate on pharmacokinetic profiles, bioavailability, and serum biochemical indices in crucian carp (Carassius carassius) following oral administration with multiple dosage levels - Sun, RuYu; Liu, YongTao; Ai, XiaoHui; Du, XiangXuan; Zhang, XiaoYi (Frontiers in Veterinary Science, 2023)
The aim of this investigation was to explore the effect of three different dose levels of emamectin benzoate (EMB) (50, 200 and 500 μg/kg bw) on pharmacokinetic characterizations, tissue distribution patterns, absolute bioavailability and serum biochemical indices in crucian carp following oral administration at 22 ± 2 ℃, respectively. The results showed that Cmax, AUC, and T1/2z after oral administration showed a dose-dependent increase in plasma. Secondary, EMB has long mean flow time (MRT) (51.88, 67.04 and 78.00 h, respectively). In conclusion, the elimination of the drug is slow, and the higher dose used, the slower elimination is. The distribution in varies tissues of crucian carp were analyzed. The order of EMB levels in tissues of crucian carp were liver > gill > kidney > muscle plus skin > plasma. As for pharmacokinetic parameters in tissues, Cmax, AUC, and T1/2z in tissues had the similar pattern as that in plasma. The absolute oral bioavailability of EMB (F%) in crucian carp was calculated to be approximately 52.70%. The serum biochemical indices including ALT and AST in experimental groups exhibited significant differences (P < 0.05) compared with control group while ALB, ALP, TP, T-CHO, BUN, GRE and GLU did not be significantly different with control group (P > 0.05).